2010
DOI: 10.1007/s00418-010-0735-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pro-inflammatory TACE-TNF-α-amphiregulin axis in Sjögren’s syndrome salivary glands

Abstract: The tumor-necrosis-factor-converting-enzyme (TACE)-TNF-α-Amphiregulin (AREG) axis plays an important pathogenic role in inflammatory and autoimmune disorders. However, the pathological roles of these proteins in the chronic autoimmune disease Sjögren's syndrome (SS) remain to be elucidated. It is known that the TACE-AREG axis is clearly part of a larger cascade of signals that starts with the activation of Furin, responsible for maturation of TACE that, in turn, determines the production of active TNF-α, direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Sisto et al (2011) conclude that failure of TNFAIP3-dependent monitoring of NF-jB signaling could explain deregulated cytokine production in SS. These results complement a recent study (by the same group) on SS, demonstrating that changes in furin, TACE (tumor necrosis-factor-converting-enzyme) and AREG (Amphiregulin) expression play a role in pro-inflammatory cytokine (TNF-a) overexpression in SS (Sisto et al 2010).…”
Section: Immune Systemsupporting
confidence: 88%
“…Sisto et al (2011) conclude that failure of TNFAIP3-dependent monitoring of NF-jB signaling could explain deregulated cytokine production in SS. These results complement a recent study (by the same group) on SS, demonstrating that changes in furin, TACE (tumor necrosis-factor-converting-enzyme) and AREG (Amphiregulin) expression play a role in pro-inflammatory cytokine (TNF-a) overexpression in SS (Sisto et al 2010).…”
Section: Immune Systemsupporting
confidence: 88%
“…Following the discovery of proinflammatory cytokines accumulation in functionally and structurally damaged areas of the salivary glands, 3,6 and its pathogenic significance in autoimmune diseases, 7,8 we assessed differences in the gene expression levels of inflammatory mediators, such as cytokines/chemokines, in human SGECs treated with the anti-Ro/SSA Abs that characterize SS. In anti-Ro/SSA Abs-treated SGEC we screened for abnormally expressed inflammatory mediators using RT 2 Profiler PCR arrays, a high-throughput technique, designed specifically to target major cytokines and chemokines.…”
Section: Tapi-1 Inhibits the Expression Of Inflammatorymentioning
confidence: 99%
“…3,4 Sjögren's syndrome is a systemic chronic inflammatory autoimmune disorder that affects secretory organs such as the salivary and lachrymal glands, 5 and TNF-a production seems to be closely linked to SS. 4,6,7 In addition, proteases such as the TNF-a converting enzyme (TACE) contribute to the autoimmune condition by processing innate inflammatory cytokines and other proteins. 8 Cytokines have a central role in triggering and perpetuating inflammation in the secretory glands, and the imbalance of pro-over anti-inflammatory cytokines results in cumulative damage to the glands impairing the secretory function.…”
mentioning
confidence: 99%
“…Importantly, Areg is induced by O 3 exposure (Vasu et al, 2010) and others have reported roles for Areg both in promoting epithelial proliferation (Lee et al, 2011) and in limiting the pulmonary inflammation induced in a bleomycin model of pulmonary fibrosis (Fukumoto et al, 2010). Areg can also be induced by TNFα (Sisto et al, 2010). …”
Section: Introductionmentioning
confidence: 99%